Vitamin D levels in the pre- and post-COVID-19 pandemic periods in pediatric patients with chronic kidney disease - Parra-Ortega, Israel; Zurita-Cruz, Jessie Nallely; Ortiz-Flores, Itzel; Romero-Navarro, Benjamin; Villasis-Keever, Miguel Angel; Martínez, Briceida López; Domínguez-Castillo, Veronica; Romo-Vázquez, José Carlos (Frontiers in Nutrition, 2023)
Introduction: Vitamin D (VD) deficiency is common in children with chronic kidney disease (CKD) because of multiple factors. During the coronavirus disease 2019 (COVID-19) pandemic, it increased because of medicine shortage and no enough medical service for patients with non-COVID-19 diseases. Objective: Toeffects of the COVID-19 pandemic-related lockdown on the serum levels and status of 25-hydroxyvitamin D3 (25-[OH]D) in children with CKD. Material and Methods: This retrospective study included patients (6-18 years old) who were diagnosed with CKD stage 2-5 and routinely measured for serum VD levels between May 2019 and December 2022. Serum 25-(OH)D levels were measured before, during, and after the pandemic (2019, 2020-2021, and 2022, respectively). The daily dose of cholecalciferol supplementation and the readjustment (if required) were recorded. Results: This study included 171 patients (median age: 12 years). Before the pandemic, the median serum VD level was 25.0 ng/mL (19.3% VD deficiency). Then, VD supplementation was adjusted to 400-1200 UI daily in 98.8% (n = 169) of patients. During the pandemic, the median VD level decreased to 22.5 ng/mL (43.3% VD deficiency). Hence, the supplementation was readjusted, and after the pandemic, the level was 28.7 ng/mL (18.7% VD deficiency), indicating a statistically significant increase in serum VD levels from the prepandemic period (p = 0.007). Conclusion: Decreased serum VD levels and increased VD deficiency frequency were observed in patients with CKD during the COVID-19 but improved after readjustment of supplementation.